Experimental and Numerical Modeling of the Extrusion Process in 1050A Aluminum Alloy for Design of Impact Energy-Absorbing Devices - Ryzińska, G.; Gieleta, R. (Проблемы прочности, 2016)
The results obtained experimentally with the use of Hopkinson bar and numerical results on backward extrusion of 1050A aluminum at 10 m/s tool speed are presented, in order to assess the extrusion technology applied in the design of energy-absorbing devices. The devices of this type should satisfy the requirements, particularly, constant force versus displacement of the piston and the amount of the energy absorbed by the object. Numerical analyses of three variants of the absorbing device geometry were presented. The obtained results allowed an appropriate selection of geometric parameters of the device, and, as a result, the requirement of the proper amount of absorbed energy was satisfied.